2015
DOI: 10.1093/jxb/erv046
|View full text |Cite
|
Sign up to set email alerts
|

The identification of Cucumis sativus Glabrous 1 (CsGL1) required for the formation of trichomes uncovers a novel function for the homeodomain-leucine zipper I gene

Abstract: The spines and bloom of cucumber (Cucumis sativus L.) fruit are two important quality traits related to fruit market value. However, until now, none of the genes involved in the formation of cucumber fruit spines and bloom trichomes has been identified. Here, the characterization of trichome development in wild-type (WT) cucumber and a spontaneous mutant, glabrous 1 (csgl1) controlled by a single recessive nuclear gene, with glabrous aerial organs, is reported. Via map-based cloning, CsGL1 was isolated and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 64 publications
5
119
0
1
Order By: Relevance
“…Mict is known to localize to the cell nucleus in onion (Allium cepa) epidermal cells when expressed heterologously (Li et al, 2015), and we also observed here that CsTTG1-GFP was localized mainly to the nucleus and plasma membrane of onion epidermal cells (Fig. 9A).…”
Section: Csttg1 Interacts With Trichome Formation Regulator Mict/csglsupporting
confidence: 80%
See 4 more Smart Citations
“…Mict is known to localize to the cell nucleus in onion (Allium cepa) epidermal cells when expressed heterologously (Li et al, 2015), and we also observed here that CsTTG1-GFP was localized mainly to the nucleus and plasma membrane of onion epidermal cells (Fig. 9A).…”
Section: Csttg1 Interacts With Trichome Formation Regulator Mict/csglsupporting
confidence: 80%
“…In cucumber, CsGA20ox1, a gene putatively encoding GA 20-oxidase, has been found to be a negative regulator of fruit spine growth, and transgenic lines with significantly increased expression of CsGA20ox1 were reported to have shorter fruit spines than the wild type (Li et al, 2015). In this study, we found that 35S:CsTTG1 transgenic lines had longer fruit spines ( Fig.…”
Section: The Csttg1 Gene Is Involved In a Regulatory Network Controllsupporting
confidence: 50%
See 3 more Smart Citations